Book review: Amita Baviskar, Uncivil City: Ecology, Equity and the Commons in Delhi. (November 2021) - Ajmal Khan A. T.,
Amita Baviskar, Uncivil City: Ecology, Equity and the Commons in Delhi . SAGE Publications, 2020, 300 pp., ₹1, 195. ISBN: 9789353289409.